Pneumococcal meningitis associated with glomerulonephritis: A case report - Vuletić, Biljana; Stojković, Andjelka; Igrutinović, Zoran; Stanković, Lidija; Medović, Raša; Dajić, Katerina; Stojković, Tanja; Janković, Marijana; Janković, Sveta S.; Vujić, Ana (Vojnosanitetski pregled, 2017)
Introduction. Streptococcus pneumoniae is the second most common cause of meningitis in children, producing more serious complications than other bacteria. Streptococcus pneumoniae infections are a rare trigger of glomerulonephritis. We presented a case of glomerulonephritis developing concurrently with meningitis in a young male child. Case report. Gross haematuria, significant proteinuria, hypertension and decreased level of C3 alongside the signs of central nervous system involvement occurred in a male patient of 5 years and 3 months of age. Spontaneous resolution of renal affliction parameters followed the successful treatment of meningitis. The disease course was strongly suggestive of postinfectious glomerulonephritis, although it manifested at the same time as meningitis. The absence of the latent period might point to the development of IgA nephropathy, but since the renal function was stable, without any abnormalities in urine tests documented during follow-up, our opinion is that this was rather the case of postinfectious nephropathy. Conclusion. The presented case is a unique clinical form of postinfectious glomerulonephritis.  An accurate diagnosis of this entity should ensure the adequate treatment and follow-up of these patients.
Keywords: pneumococcal infections; streptococcus pneumoniae; child; meningitis; glomerulonephritis; diagnosis